Evaluation committees at work: knowing the processes to support them - Lisimberti, Cristina; Montalbetti, Katia (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2018)
The L.107 / 2015 has redefined the composition and tasks of the evaluation committees, which are responsible for identifying criteria for teachers’ merit (bonus). This action, innovative at the national level, challenges those who deal with the evaluation of and in school contexts. The survey here presented takes origin from a knowledge question, aimed to investigate how this novelty has been implemented, and from a training concern aimed to give support to schools involved in this process. The data coming from an on-line questionnaire filled by to school principals in Lombardy confirm the successful start-up of the activities and, at the same time, highlight schools’ specific needs for methodological support.